Cucumis sativus L. Seeds Ameliorate Muscular Spasm-Induced Gastrointestinal and Respiratory Disorders by Simultaneously Inhibiting Calcium Mediated Signaling Pathway - Muqeet Wahid; Fatima Saqib; Hanadi Talal Ahmedah; Claudia Mihaela Gavris; Vincenzo De Feo; Mircea Hogea; Marius Moga; Radu Chicea (MDPI AG, 2021)
Cucumis sativus L. is globally cultivated as an edible vegetable. Besides its nutritional benefits, it is used in traditional medicines against various ailments. The current study was designed to elucidate the multi-target mechanisms of a C. sativus seeds extract against asthma and diarrhea using network pharmacology along with a molecular docking approach. Furthermore, in-vitro and in-vivo experiments were conducted to verify the mechanistic insight of in silico studies. LC-ESI-MS/MS was performed to identify the bioactive compounds in the extract; later, some compounds were quantified by HPLC. C. sativus seed. EtOH has kaempferol in higher concentration 783.02 µg/g, followed by quercetin (693.83 µg/g) and luteolin (617.17 µg/g). In silico studies showed that bioactive compounds interfered with asthma and diarrhea-associated target genes, which are members of calcium-mediated signaling to exert a calcium channel blocker activity. The seeds extract exerted a concentration-dependent spasmolytic response on isolated jejunum, trachea, and urinary bladder preparations and caused relaxation of spastic contraction of K+ (80 mM) with suppressed calcium concentration-response curves at dose 0.3 and 1 mg/mL. It also showed antiperistalsis, antidiarrheal and antisecretory activity in animal models. Thus, C. sativus seeds have therapeutic effects by regulating the contractile response through a calcium-mediated signaling pathway.